2015
DOI: 10.1097/cad.0000000000000229
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrocostus lactone suppressed the proliferation, migration, and invasion of colorectal carcinoma through the downregulation of eIF4E expression

Abstract: Dehydrocostus lactone (DHC) is the main active ingredient extracted from a traditional Chinese medicine called Radix Aucklandiael. A few studies recently showed that DHC has anticancer potential. However, no reports exist as yet on the effects of DHC on colorectal carcinoma (CRC). This study aimed to determine whether and how DHC functions in CRC cells. After treatment with DHC, both Lovo and SW480 cells were significantly inhibited in their proliferation, cell cycle progression, migration, and invasion abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…MAPKs are also logical and known regulators for cell translation processes [25] that may be controlled by the Ras/MNK and PI3K/Akt cascades [28]. Indeed, overexpression of eIF4E in many cancers caused elevated cell proliferation and migration, whereas eIF4E knockdown suppressed the proliferation, migration, and invasion of several cancers [18,31]. Previous studies [18,19] have also reported that eIF4E has an important role in cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…MAPKs are also logical and known regulators for cell translation processes [25] that may be controlled by the Ras/MNK and PI3K/Akt cascades [28]. Indeed, overexpression of eIF4E in many cancers caused elevated cell proliferation and migration, whereas eIF4E knockdown suppressed the proliferation, migration, and invasion of several cancers [18,31]. Previous studies [18,19] have also reported that eIF4E has an important role in cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…AUX1 and PINs have been demonstrated to play important roles in polar auxin transport as an influx and efflux carriers, respectively [4,[11][12][13][44][45][46][47]. In etiolated pea seedlings, PsAUX1 and PsPIN1, PsPIN2 and PsPIN3 have been isolated [27][28][29][30][31][32][33][34][35][36][37][38][39]46,47]. Semiquantitative RT-PCR analysis revealed that DHCL substantially reduced accumulation of mRNA both of PsAUX1 and PsPIN1 in the etiolated pea seedlings (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A number of germacranolide-type sesquiterpene lactones with an α-methylene-γlactone derivatives obtained from natural sources have been demonstrated to exhibit pharmaceutically interesting biological activities in animals and plants. DHCL and costunolide have been demonstrated to show antitumor activity, anti-inflammatory activity, and the induction of apoptosis [26][27][28][29][30][31][32]. These compounds are also demonstrated to act as germination stimulants for the root parasitic broomrapes Orobanche cumana Wallr.…”
Section: Introductionmentioning
confidence: 99%
“…DHC was found to induce mitochondrial intrinsic apoptosis with enhanced pro-apoptotic effects of DOX in both cell lines. DHC was shown to induce apoptosis in liver [ 9 , 10 ], breast [ 11 , 12 ], leukemia [ 13 ], prostate [ 14 ], ovary [ 15 ], colon [ 16 ], and bladder cancer [ 17 ]. DHC caused reduction in HIF-1α levels in A549 and H460 cells followed by suppression of the levels of Akt and pAkt, GSK-3β and pGSK-3β, and mTOR and p-mTOR.…”
Section: Discussionmentioning
confidence: 99%
“…DHC has been used to treat various diseases, including prevention of various types of cancers, such as liver cancer [ 9 , 10 ], breast cancer [ 11 , 12 ], leukemias [ 13 ], prostatic cancer [ 14 ], ovarian cancer [ 15 ], colorectal cancer [ 16 ], and bladder cancer [ 17 ]. DHC mediates anti-cancer effects by interacting mechanisms like inhibition of telomerase activity, induction of cellular apoptosis pathways (mitochondrial intrinsic and death-receptor dependent extrinsic), induced endoplasmic reticulum (ER) stress [ 18 ], and limiting migration-invasion and metastasis [ 8 , 16 , 19 ]. DHC prevents growth of various types of cancer by specific mechanisms like tumor necrosis factor (TNF)-α-induced degradation and phosphorylation of IkBa [ 20 ], inhibition of signal transducers, and activators of transcription 3 (STAT3) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%